Defining civil and political rights : the jurisprudence of the United Nations Human Rights Committee - Conte, Alex, 1971-; Burchill, Richard (Farnham, Surrey, England ; Burlington, VT : Ashgate, 2009)
"Defining Civil and Political Rights provides a comprehensive analysis and commentary on the decisions - technically known as views - of the United Nations Human Rights Committee, for use by human rights lawyers throughout the world. Each of the substantive rights and freedoms set out in the International Covenant on Civil and Political Rights is considered in detail, by analysis of final reviews and comments of the Human Rights Committee." "This second edition has been thoroughly revised and updated to take account of recent jurisprudence on the Human Rights Committee. New material has been added based upon substantive areas of the committee's jurisprudence."--BOOK JACKET.
Introduction / Alex Conte and Richard Burchill -- Procedure under the optional protocol / Alex Conte -- Limitations to and derogations from covenant rights / Alex Conte -- Democratic and civil rights / Alex Conte -- Security of the person / Alex Conte -- The judicial process / Alex Conte -- Privacy, honour and reputation / Alex Conte -- Rights of the family and the children / Richard Burchill -- Self-determination / RIchard Burchill -- Minority rights / Richard Burchill -- Equality and non-discrimination / Richard Burchill.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: United Nations. -- Human Rights Committee; Human rights -- Cases; Electronic books